2009
DOI: 10.1111/j.1525-1470.2009.00918.x
|View full text |Cite
|
Sign up to set email alerts
|

Generalized Pustular Psoriasis in a 6‐week‐old Infant

Abstract: Generalized pustular psoriasis (GPP) is rare in childhood, especially in early infancy. At this young age, it is essential to make an accurate diagnosis as pustules could be the presentation of serious infectious diseases or unusual dermatologic diseases. We reported clinical manifestations, laboratory examinations, and histopathology findings in a 6-week-old girl with GPP. Acitretin was initiated at 1 mg/kg/day with marked improvement on her psoriasis, and titrated to 0.4 mg/kg/day in the subsequent 6 months … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
23
0
1

Year Published

2011
2011
2019
2019

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 31 publications
(25 citation statements)
references
References 5 publications
0
23
0
1
Order By: Relevance
“…The information was available for all interventions within 3 months of therapy initiation, between 3 and 6 months for nine (35%) interventions, and after 6 months for six (23%) interventions. The most commonly used therapies to control pediatric GPP were acitretin, CyA, and MTX . All patients received one of these three medications at some point during the course of their disease, although in some cases information was mentioned as “previously used therapies” or a detailed description was not provided.…”
Section: Resultsmentioning
confidence: 99%
“…The information was available for all interventions within 3 months of therapy initiation, between 3 and 6 months for nine (35%) interventions, and after 6 months for six (23%) interventions. The most commonly used therapies to control pediatric GPP were acitretin, CyA, and MTX . All patients received one of these three medications at some point during the course of their disease, although in some cases information was mentioned as “previously used therapies” or a detailed description was not provided.…”
Section: Resultsmentioning
confidence: 99%
“…4 In the present review, eight new studies on the use of retinoids were identified. [27][28][29][30][31][32][33][34] Five studies were excluded because of systemic anti-psoriatic combination therapy 27,[30][31][32][33] and one study because of an unclear treatment regimen. 34 One case report 28 (LOE5) described clearance after 6 weeks of treatment with acitretin 1 mg/kg/day in a 6-weeks-old girl with generalized pustular psoriasis (GPP); safety data were not reported.…”
Section: Retinoidsmentioning
confidence: 99%
“…The dose of acitretin was reduced to 0.4 mg/ kg/day during this period and was stopped after one month, no relapse was seen in the next month (Chao, Cheng, & Chung, 2009). The dose of acitretin was reduced to 0.4 mg/ kg/day during this period and was stopped after one month, no relapse was seen in the next month (Chao, Cheng, & Chung, 2009).…”
Section: Ergin Et Al Reported a Case Of Infantile Pustular Psoriasismentioning
confidence: 99%
“…The patient's skin was normal after 6 weeks and there was no flare in the following 6 months. The dose of acitretin was reduced to 0.4 mg/ kg/day during this period and was stopped after one month, no relapse was seen in the next month (Chao, Cheng, & Chung, 2009).…”
Section: Salleras Et Al Reported a Case Of A 4-year-old Girl With Comentioning
confidence: 99%